2009
DOI: 10.1158/0008-5472.can-09-0462
|View full text |Cite
|
Sign up to set email alerts
|

17-Hydroxy-jolkinolide B Inhibits Signal Transducers and Activators of Transcription 3 Signaling by Covalently Cross-Linking Janus Kinases and Induces Apoptosis of Human Cancer Cells

Abstract: Constitutive activation of the Janus kinase (JAK)/signal transducer and activator of transcription (STAT) pathway occurs frequently in cancer cells and contributes to oncogenesis. Among the members of STAT family, STAT3 plays a pivotal role in the development and progression of human tumors. The STAT3-mediated signaling pathway has been recognized as a promising anticancer target. Here, we show that 17-Hydroxy-jolkinolide B (HJB), a diterpenoid from the Chinese medicinal herb Euphorbia fischeriana Steud, stron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 46 publications
1
62
0
Order By: Relevance
“…It irreversibly inhibits IκB kinase and induces apoptosis of tumor cells (Yan et al, 2008). Furthermore, 17-Hydroxy-jolkinolide B strongly inhibits IL-6-induced as well as constitutive STAT3 activation, which inhibits growth and induces apoptosis of tumor cells (Wang et al, 2009). In the current study, we investigated the in vitro effects of Jolkinolide B on cell growth and death in U937 cells, human histiocytic lymphoma cell lines, and examined the mechanisms underlying its actions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It irreversibly inhibits IκB kinase and induces apoptosis of tumor cells (Yan et al, 2008). Furthermore, 17-Hydroxy-jolkinolide B strongly inhibits IL-6-induced as well as constitutive STAT3 activation, which inhibits growth and induces apoptosis of tumor cells (Wang et al, 2009). In the current study, we investigated the in vitro effects of Jolkinolide B on cell growth and death in U937 cells, human histiocytic lymphoma cell lines, and examined the mechanisms underlying its actions.…”
Section: Discussionmentioning
confidence: 99%
“…Euphorbia fischeriana Steud has long been used as a folk medicine to treat cancer in China. Early chemical investigation showed that the plant contains diterpenoids, triterpenoids and steroids including two ent-abietane diterpenoids, jolkinolide A and B, which exhibit significant antitumour activities against several tumour lines such as Sarcoma 180 and Ehrlich ascites carcinoma in mice (Wang et al, 2009). Previous study has shown that Jolkinolide B from the roots of Euphorbia fischeriana Steud could induce apoptosis in human chronic myeloid leukemia K562 cells (Luo, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…HJB has no activity on the platelet-derived and epidermal growth factor, or insulin-like growth factor 1 signalling pathways, therefore its effect is highly specific. 89 Yan et al investigated the antitumor effects of 17-acetoxyjolkinolide B and 6…”
mentioning
confidence: 99%
“…Our results demonstrated that bigelovin inhibited JAK2 activity with an IC 50 of 44.24 Bigelovin inhibited JAK/STAT3 signaling in a thiol-dependent manner Bigelovin contains an α, β-unsaturated carbonyl group and an α-alkene-γ-lactone, which are reactive with thiols. Previous studies have shown that covalent modification of certain cysteine thiol groups of JAK2 by small molecule compounds could lead to JAK2 inactivation [31,32] . Therefore, we speculated that bigelovin may react with thiols of the cysteines in the JAK2 protein.…”
Section: Resultsmentioning
confidence: 99%